"It's our future." Youth and fracking justice in England. Issue 1 (2nd January 2021) - Dunlop, Lynda; Atkinson, Lucy; Turkenburg-van Diepen, Maria
ABSTRACT: Youth perspectives on energy interventions are rarely sought or acted on in local and national policy, despite the stake young people have in the future created by today's energy and environmental policies. The debate on unconventional shale gas development (hydraulic fracturing, or "fracking") is one context in which decisions taken today have long-term, intergenerational consequences, with environmental justice intersecting with energy needs. This study investigated young people's perceptions and experiences of exploratory fracking and associated political processes in order to understand their experiences of environmental justice. In depth, qualitative field research was conducted with 84 young people in locations within 20 miles (32 kilometers) of operational exploratory fracking sites prior to the moratorium in England announced in November 2019. Data were analysed with attention to recognition, participation and distributional justice. Young people experienced environmental, democratic and social injustices through lack of recognition of their aims and values as both youth and members of a rural community, and exclusion from formal participation in decision-making. Young people saw economic and thus environmental power residing with industry closely tied to national government, and experienced a tension between desire to trust institutional authority and betrayal by these same institutions. We argue that this case study of young people in "the sacrifice zone" demonstrates a connection between depoliticisation and anti-politics, and that these processes undermine trust in democracy. There is a need for recognition and meaningful inclusion of young people and local communities in decision-making, particularly where the consequences of the decisions last for generations.